GramGen : a Genetic Programming System Based on Context Free Grammar - Quirin, Arnaud; Korczak, Jerzy (GramGen : system programowania genetycznego oparty na gramatyce bezkontekstowej, 2010)
In this paper, a new genetic programming system, called GramGen, is described. The system combines context free grammar (CFG) with genetic programming and uses an extended operator set. The objective of the grammar is to limit the size of the search space by allowing the user to define constraints related to the structure or the simplicity of the discovered formulas. These constraints are taken into account by the use of specific genetic operators. The experiments show that the proposed system allows users not only to discover new knowledge but also improve the performance of existing ones.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 128-147
Keywords: genetic algorithm; genetic operators; context free grammar; knowledge discovery; evolution-based software